Ecological and Agrotechnical Aspects of Cultivation of Salvia sclarea L. Under Conditions of Drip Irrigation in the South of Ukraine - Victor Chaban (Polish Society of Ecological Engineering (PTIE), 2021)
Salvia sclarea L. is a commercially important crop from the Lamiaceae family, the raw material of which serves as a source of valuable essential oil. Effects of fertilizers, ploughing depth, time of sowing and row spacing on the productivity of nutmeg sage grown under conditions of drip irrigation were investigated in the field experiments conducted on meadow-chestnut residual-saline medium-loam soils of the southern Ukraine. It was found that time of sowing and fertilizer dose had a greater impact on the productivity of sage than row spacing and ploughing depth. Regarding the duration of S. sclarea L. cultivation, it was determined that within the first three years the inflorescence yield ranged from 9.98–10.62 t/ha, and in the fourth year – decreased by 6.8 times, amounting to 0.74–1.74 t/ha. The maximum productivity of the plant was achieved in the second year of cultivation during the winter sowing period with row spacing of 45 cm, ploughing depth of 28–30 cm and dose of N60P90 fertilizer of 15.01 t/ha. With the same ploughing depth and dose of N60P90 fertilizer, high level of productivity, 14.74 t/ha, was also achieved when row spacing of 70 cm was used. Application of mineral fertilizers at doses similar to N60P90 under the main tillage during winter sowing period resulted in 51.1 kg/ha and 51.3 kg/ha yields of essential oil in the first and second years of cultivation, respectively. In the third and fourth years, the yields dropped to 33.3 kg/ha and 8.7 kg/ha or by 35.1% and 83.0%, respectively. During spring sowing period, the yield of essential oil was in the range of 19.2–24.6 kg/ha in the first three years, but in the fourth year – decreased to 6.5 kg/ha or by 73.6%. Therefore, to obtain inflorescence yield of nutmeg sage at the level of 14.5–15.0 t/ha with essential oil yield of 51.0 kg/ha in arid climates, it is recommended to use drip irrigation, row spacing of 45 cm, ploughing depth of 28–30 cm, fertilizer at a dose of N60P90 and sowing time in the first ten-day period of December (winter period).